2009
DOI: 10.1088/0957-4484/20/21/215603
|View full text |Cite
|
Sign up to set email alerts
|

Room temperature synthesis of K2Mo3O10·3H2O nanowires in minutes

Abstract: Polyoxometalates have been widely used in the fields of catalysis, analytical chemistry, biochemistry, medicine and synthesis of novel organic-inorganic materials. It is difficult to synthesize pure polymolybdate products from a solution because several kinds of molybdenum-based anions may coexist. As a result, varied acidification methods are commonly used for solution synthesis of polymolybdates. In this paper we report an approach for the synthesis of [001]-oriented K(2)Mo(3)O(10)x3H(2)O nanowires from an a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…• C in the whole reaction process. This was attributed to the existence of NH 4 + ions in the solution [38,39]. Synthesized under this condition, the end products were uniform and long nanowires, as shown in Figure 1(e).…”
Section: Resultsmentioning
confidence: 86%
“…• C in the whole reaction process. This was attributed to the existence of NH 4 + ions in the solution [38,39]. Synthesized under this condition, the end products were uniform and long nanowires, as shown in Figure 1(e).…”
Section: Resultsmentioning
confidence: 86%
“…So far, dipotassium molybdates have been extensively used in the synthesis of solid‐state laser materials, e.g. K 2 Mo 3 O 10 , and have been used as catalysts in the growth of high‐quality single crystals, such as Yb x Y 1− x Al 3 (BO 3 ) 4 …”
Section: Introductionmentioning
confidence: 99%
“…So, these particles are easily absorbed by an animal's digestive system. Many studies [6][7][8][9] have indicated that nanocrystalline metals assist fast growth and enhance production of animals. The synthesized nanoscale metals will presumably replace inorganic minerals (sulphates and oxides) in animal diet, although under the form of sulfate salts or chelates inorganic minerals have been applied widely [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…In Vietnam, most minerals supplemented into animal feed are in the form of inorganic salts that lead to low feeding efficiency, causing waste and environmental pollution. Recently, there have been some studies [7,9,11,12] which prefer the application of nanoscale metals instead of inorganic minerals for animal feed. Presumably, introducing nanoscale metal preparations into poultry farming is essential in improving the meat and egg productivity.…”
Section: Introductionmentioning
confidence: 99%